2014
DOI: 10.3138/ptc.2013-17
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Trained Dog as a Gait Aid for Clients with Ataxia: A Case Report

Abstract: Purpose: To illustrate the use of a trained dog as a therapeutic tool to optimize physical and psychosocial adaptation of clients with ataxia. Method: The gait pattern and gait speed of two people with cerebellar ataxia using different gait aids, including a trained intervention dog and an assistance dog, were compared. Participants' experience of working with the dogs was documented via semi-structured interviews. Results: The use of an intervention dog as part of rehabilitation allowed clients to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…When walking with a mobility dog in heel position, the individual does not move or lift the arm to reposition the device when moving through the environment; rather, the arm stays in constant contact with a stable "surface" (i.e., harness handle) as the dog moves through the environment. This is consistent with prior research suggesting that mobility dogs require fewer movements for use when compared to traditional mobility devices such as canes, which may make them preferable for people with disabilities that impact their ability to produce coordinated, controlled movements [14,16].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…When walking with a mobility dog in heel position, the individual does not move or lift the arm to reposition the device when moving through the environment; rather, the arm stays in constant contact with a stable "surface" (i.e., harness handle) as the dog moves through the environment. This is consistent with prior research suggesting that mobility dogs require fewer movements for use when compared to traditional mobility devices such as canes, which may make them preferable for people with disabilities that impact their ability to produce coordinated, controlled movements [14,16].…”
Section: Discussionsupporting
confidence: 90%
“…Blanchett et al found that, among persons with various physical disabilities who were ambulatory, mobility dog partnership resulted in improved performance on the 10-m walk test, the timed up-and-go (TUG) test, and the stair ascent test [13]. In a case study by Abbud et al involving two individuals with ataxia, mobility dog partnership was shown to improve walking patterns and promote safer, more independent mobility [14]. Research by Rondeau et al examining the results of an intervention involving a trained "rehabilitation dog" concluded that all four study participants (stroke survivors) demonstrated improved walking speed and gait patterns when ambulating with the rehabilitation dog versus with a cane [15].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of occupational therapy after spinal cord injury, Thompkins et al (2019) found lower negative affect when a dog was integrated into the therapy than in a control group without a dog. Dogs may also be able to assist gait training, as suggested by two small case studies, which found faster improvement when the person trained with a dog than with the traditional stick (Abbud et al, 2014; Rondeau et al, 2010). A dog-handler team may also be integrated into the health professional’s approach for retraining clients’ hand and speech functions after a paresis.…”
Section: Animal-assisted Therapymentioning
confidence: 99%
“…In addition to technology, some studies on walking assistance using dogs and handkerchiefs have also been reported. Walking with a rehabilitation dog that has been specifically trained for goal-directed interventions or with an assistance dog that helps people with physical disability and mobility impairments has been reported to improve balance while walking in patients with SCD [116]. Furthermore, the handkerchief-guided gait, in which the patient with SCD walks along with the caregiver while maintaining light tension on a handkerchief by pulling lightly, has been shown to decrease body swaying and increase stride length and gait velocity during walking [117].…”
Section: Assistive Technologymentioning
confidence: 99%